Effect of Bank Health Level (Using Rgec Method) on Profit Growth - Henry Wijaya, John; Minda Utami, Eristy; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Indonesian banking is faced with various problems. One of them is an increase in the 7-Day Reverse Repo Rate (7-DRRR). In May-June 2019, Bank Indonesia (BI) raised this by using a basic 75 basis points. This increase in benchmark interest will affect the banking business. 7-DRR will affect economic growth. Even though economic growth greatly influences the demand for credit. The increase in 7-DRR encourages banks to increase deposit interest and credit interest (cnbcindonesia.com). When economic growth is weak, credit demand will weaken. The increase in credit interest will also make banks face various problems that will certainly affect profits because banks are considered not as healthy and in prime condition as usual.